Synthesis of chiral crown ethers derived from d-galactose and their application in enantioselective reactions. Issue 30 (26th July 2019) - Rapi, Zsolt; Nemcsok, Tamás; Bagi, Péter; Keglevich, György; Bakó, Péter
Abstract: A few new α- and β-d -galactopyranoside-based chiral lariat ethers of monoaza-15-crown-5 type were synthesized. These macrocycles proved to be efficient catalysts in a few asymmetric reactions under mild phase transfer conditions. The catalytic effect of the lariat ethers with methoxy, ethoxy, isopropoxy and aryloxy substituents on the C-1 of the sugar unit in both α and β positions was compared. In the presence of β-d -galactopyranoside-based crown ethers, the asymmetric Darzens condensation of α-chloroacetophenone and benzaldehyde, the epoxidation of trans -chalcone, the cyclopropanation (MIRC reaction) of benzylidenemalononitrile and 2-benzylidene-1, 3-indandione with diethyl bromomalonate were performed with enantioselectivities of 61%, 64%, 86% and 96%, respectively. In all reactions, the β-anomers were more efficient in terms of enantioselectivity than the α forms. Graphical abstract: Image 1